Robotic Devices for Minimally Invasive Endovascular Interventions: A New Dawn for Interventional Radiology. (22nd February 2021) - Gunduz, Seyda; Albadawi, Hassan; Oklu, Rahmi
Abstract : Endovascular Interventions In article number 2000181, Rahmi Oklu and co‐workers provide a critical evaluation on the emerging robotic technologies for minimally invasive endovascular interventions. The cover image demonstrates a thrombosed vessel along the axilla of the right arm. In the middle, the image presents magnetically controlled microbots that are rotating at high frequency to break down the clot into small fragments; microbot directed thrombectomy. In the right circle panel, a magnified image of a microbot is shown rotating at high frequency.